Barnyard grass (Echinochloa crus-galli L.) as a candidate plant for phytoremediation of arsenic from arsenic-amended and industrially polluted soils - Sultana, Razia; Ahmed, Tamim; Islam, Shah Mohammad Naimul; Uddin, Md Nizam (Frontiers in Soil Science, 2022)
The potentiality of barnyard grass for remediation of arsenic (As)-contaminated soil has been reported in several research works. However, the phytoremediation ability of barnyard grass from industrially polluted multimetal-contaminated soil in comparison to As-amended soil needs to be elucidated. This work investigated the As remediation potentiality of barnyard grass from As-amended and industrially polluted soils, and the fractionation of As was done in soils with plants and without plants grown. The result showed that at the highest As level in the soil, barnyard grass accumulated the highest amount of As in both the root (414.81 mg kg-1) and shoot (114.12 mg kg-1). However, barnyard grass produced the highest amount of biomass in industrially polluted soil that resulted in the highest amount of As uptake. Moreover, barnyard grass also accumulated lead (Pb) and chromium (Cr) from industrially polluted soil. The bioaccumulation factor (BF) of As was >1 in As-amended soil in all the treatments as well as in industrially polluted soil. Fractionation of As in post-harvest soil revealed that compared to soil without plants grown, As in the soil was reduced from residual As (F5); As associated with well-crystallized hydrous oxides of iron (Fe) and aluminum (Al) (F4); As associated with amorphous and poorly crystallized hydrous oxides of Fe and Al (F3), whereas a slight increase was found in non-specifically sorbed As (F1) and specifically sorbed As (F2) due to the plant’s effect. The slight increase in the concentration of As in F1 and F2 fractions contributed to the bioavailable forms of As in the rhizosphere and sustained As concentration for further plant uptake. The maximum plant growth and highest uptake of As in the industrially polluted soil revealed the potentiality of barnyard grass for remediation of multimetal-polluted soil.